European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on Stress Testing of Banks. (IMF Staff Country Reports; Country Report ;, 2013)
This article summarizes the European Union's stress testing exercises and future priorities. The 2011 solvency stress testing was marked by methodology and data. The exercise forced banks to increase the quality and quantity of capitalization. This test has many controversial issues, but the benefits of this bold approach overshadow the risks. Several stress testing exercises have filled the pages of literature; an additional stress test is reviewed here.